Menanamkan Perilaku Hidup Hemat Pada Anak Sejak Dini - Andi Aslindah; Nur Indahsari (Communio: Jurnal Pengabdian Kepada Masyarakat, 2022)
Inculcating a frugal lifestyle from an early age in children is very important to be applied by parents. Frugal living is not always related to money, but frugal living can include many things. For example, saving on water and electricity. Parents need to set an example and a good understanding of the concept in moderation and do not need to overdo it when they want or use something. However, instilling frugal living behavior in early childhood is not an easy job. Because in reality, not a few parents complain that they have to spend a lot of pocket money on their children. But on the other hand, sometimes parents also don't have the heart to refuse their child's wishes. Therefore, parents need to understand what tricks need to be done in instilling the habit of living frugal behavior in children from an early age.